SCREEN PRINTED ELECTRODE OF CARBON NANOTUBES MODIFIED WITH GOLD NANOPARTICLES FOR SIMULTANEOUS DETERMINATION OF ZINC, LEAD AND COPPER - JUAN CLAUDIO MANCILLA GAMBOA (Journal of the Chilean Chemical Society, 2020)
Differential pulse anodic stripping voltammetry, method used for simultaneous determination of zinc, copper and lead with screen printed electrode of carbon nanotubes modified with gold nanoparticles was investigated. The results indicate that a simultaneous identification and quantification of zinc, lead and copper is possible at -0.6 V, -0.26 V and 0.16 V respectively. The maximum current was linearly dependent on the concentration of Zn2+, Pb2+ and Cu2+, thus allowing the construction of analytical curves, being: -Ip (A) = 0.08 + 0.214 [Zn2+ (g L-1)]  in a range of 9.9 to 120 mg L-1 with an R2 = 0.993; -Ip (A) = -1.06 + 0.240 [Pb2+ (mg L-1)] in a range of 9.9 to 120 mg L-1 with an R2 = 0.998; -Ip (A) = -10.93 + 15.16 [Cu2+ (mg L-1)] in a range of 0.99 to 12 mg L-1 with an R2 = 0.998. The limits of detection and quantification were estimated between 1.0 - 3.5 mg L-1 for Zn2+, 1.5 - 5.0 mg L-1 for Pb2+ and 0.1 - 0.33 mg L-1 for Cu2+. An integral, selective and reliable system for simultaneous determination of heavy metals was achieved, which may have applications in field monitoring for environmental use and public health.